Antioxidative effect of Arthrospira platensis biomass on the lipid oxidation - Dayane Meireles de Souza; Jorge da Silva Pinho Junior; Vanessa Naciuk Castelo Branco; Kátia Gomes de Lima Araujo; Beatriz do Nascimento Corrêa dos Santos; Josiane Roberto Domingues (Fundação Oswaldo Cruz (FIOCRUZ), 2017)
Introduction: Cyanobacteria are promising natural sources of antioxidants. Environmental conditions that influence synthesis of substances in cultures of cyanobacteria have been studied. Objective: This investigation aimed to evaluate the antioxidative effect of Arthrospira platensis biomass on the process of lipid oxidation in bulk oil and oil/water emulsion. Method: Arthrospira platensis growth potential for antioxidant production under different cultivation conditions using an experimental design. The antioxidative effect of the methanolic extracts and the biomass on preventing lipid oxidation was measured by peroxide value (PV). Results: The results showed that the growing conditions to obtain the biomass promoted change in the protective ability of different biomass extracts. Extracts obtained from the cultivated biomass grown under 150 μmol photons/m2s-1, 1.875 g.L-1 NaNO3; 13.5 g.L-1 NaHCO3 (assay14) and 50 μmol photons/m2s-1, 2.5 g.L-1 NaNO3; 18.0 g.L-1 NaHCO3 (standard)  showed the most antioxidative effect on preventing lipid oxidation, therefore used in the formulation of mayonnaise. The mayonnaise made with soybean oil and 0.5% biomass was preserved against lipid photodegradation during seven days of storage, but the peroxide value related to control varied from 2.9 to 3.1 mEqO2.Kg-1, with no significant difference in the preservation afforded by tert-butilhydroquinone, in the same period of storage. In mayonnaise made with sunflower oil, biomass, independent of concentration, was unable to protect the product against photooxidation. Conclusions: The results demonstrate the protective ability on preventing lipid oxidation of Arthrospira platensis biomass and its potential for use in food lipid-based of soybean oil.